Fenomenologi Curhat Digital: Pemaknaan Komunikasi Interpersonal Generasi Z Melalui ChatGPT Sebagai Media Cerita - Azzahrah Miftahul Jannah; Dani Kurniawan; Noor Afy Shovmayanti (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of artificial intelligence, particularly ChatGPT, is not only used as an academic tool, but also increasingly used as a digital confidant by Generation Z. This study aims to explore Generation Z's interpretation of interpersonal communication in using ChatGPT as a storytelling medium, focusing on aspects of self-disclosure, emotional security, dependency levels, and gender influence. This study uses a descriptive qualitative method with a phenomenological approach. There were six informants, all students at Muhammadiyah University Klaten, who were selected through purposive sampling. Data collection was conducted through open questionnaires and in-depth interviews, then analyzed by grouping the themes of the informants' subjective experiences. The results showed that four informants used ChatGPT as a digital confidant, while the other two informants used ChatGPT solely for academic purposes. Informants who used ChatGPT as a confidant felt that it was easy to express their emotions, had a higher level of openness, and felt emotionally secure due to the minimal risk of social judgment. The level of attachment to ChatGPT varied, ranging from situational use to a tendency toward more intense emotional attachment. Additionally, it was found that gender also influenced the meaning of ChatGPT usage, with female informants more dominant in utilizing ChatGPT as a confessional medium compared to male informants. This study concluded that ChatGPT is perceived as a temporary safe space in digital